2022
DOI: 10.1101/2022.07.05.22277189
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Class switch towards non-inflammatory IgG isotypes after repeated SARS-CoV-2 mRNA vaccination

Abstract: Repeated mRNA vaccinations are an efficient tool to combat the SARS-CoV-2 pandemic. High levels of neutralizing SARS-CoV-2-antibodies are an important component of vaccine-induced immunity. Shortly after the first or second mRNA vaccine dose, the IgG response mainly consists of the pro-inflammatory isotypes IgG1 and IgG3 and is driven by T helper (Th) 1 cells. Here, we report that several months after the second vaccination, SARS-CoV-2-specific antibodies were increasingly composed of non-inflammatory IgG2 and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 91 publications
2
6
2
Order By: Relevance
“…Supporting evidence stems from another study, where comparable results were observed, additionally with a further increase of IgG4 after the third vaccination with BNT162b2 (74). Similarly to our results, no IgG4 response was detected after two AZD1222 vaccinations.…”
Section: Discussionsupporting
confidence: 92%
“…Supporting evidence stems from another study, where comparable results were observed, additionally with a further increase of IgG4 after the third vaccination with BNT162b2 (74). Similarly to our results, no IgG4 response was detected after two AZD1222 vaccinations.…”
Section: Discussionsupporting
confidence: 92%
“…Plasma observations are similar to those reported in recent studies. 42 Since B-cells undergo the class switching pattern of IgM>IgG3>IgG1>IgA>IgG2>IgG4, 48 the IgG4 dominance we observed suggest enhanced maternal B-cell class switching. Our study results align with a study that showed an increase in IgG4 with pregnancy and higher IgG4 response in the pregnant population when compared to non-pregnant individuals.…”
Section: Results In the Context Of What Is Knownmentioning
confidence: 73%
“…24 Our results confirm earlier conclusions that the initial two dose vaccination series during gestation resulted in appreciable RBD-specific IgG response in maternal circulation, UCB, and breastmilk. 20, 27 Importantly, longitudinal analysis of post-partum samples indicates that the booster dose is essential for producing higher and more durable antibody levels in both maternal circulation and breastmilk, 28, 29, 42 and should be strongly encouraged for all pregnant people to increase neonatal passive immune protection against SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 99%
“…The beads were resuspended in 1 mL of FACS buffer for flow cytometry. To measure ADCP, the phagoscore 7 was calculated as a fraction of bead-positive cells multiplied by the mean fluorescence intensity (MFI, Supplementary Figure 1 A, B). For ADCD, the MFI was used (Supplementary Figure 1 C,D).…”
Section: Measurement Of Adcp and Acdcmentioning
confidence: 99%
“…The affinity of IgG for Fc-mediated functions is determined by the isotype (subclass) and the conserved n-297 glycosylation site 5,6 . Several studies have investigated the long-term changes in the IgG profile of mRNA vaccines, showing an increased contribution of the IgG4 subclass of anti-S IgG [7][8][9] associated with weaker Fc-mediated functions 7 (7). In Taiwan, a domestically developed protein subunit vaccine against COVID-19 was developed and administered (Medigen MVC-COV1901) 10,11 .…”
Section: Introductionmentioning
confidence: 99%